Ten year challenge with Ponseti method for clubfoot: our experience - Dibello, Daniela; Colin, Giulia; Galimberti, Anna Maria Chiara; Di Carlo, Valentina (Acta Biomedica Atenei Parmensis, 2019)
Equino-varus-adducted-supinated, also known as clubfoot, is the most frequent congenital malformation of the foot. Scientific evidences of the last decades has definitively confirmed the efficacy of the non-invasive Ponseti Technique, which is based on manipulation, plaster casts, percutaneous achillean tenotomy and stabilization of the foot using a brace. The aim of the article is to describe the experience of our third level hospital in treating clubfoot with Ponseti Method. Our data are similar to the ones in literature, confirming the effectiveness and good reproducibility of the Method.